Assessing delivery and business models for high impact digital solutions at scale: the case of Rwanda Smart Nkunganire System (SNS) - Sartas, M.; Mudereri, B.T.; Senge, M.; Rabourn, T.R.; Ogunsami, T.; Uzamushaka, S.; Kihoro, E.; Kangethe, E.; Muzata, B.S.; Guchu, W.; Kamau, N. E. (International Institute of Tropical Agriculture, 2024)
The Smart Nkunganire System (SNS) in Rwanda is a groundbreaking digital platform that has revolutionized the delivery of agricultural inputs to farmers, significantly impacting the nation’s agricultural landscape. By leveraging mobile technology and a centralized database, the SNS has streamlined the Rwandan government’s subsidy allocation process, enabling over 1.9 million farmers to access essential inputs like fertilizers and seeds. The system’s real-time data tracking, farmer empowerment tools, and market development initiatives have fostered transparency, efficiency, and inclusivity in the agricultural sector. Despite its successes, the SNS faces challenges in areas such as digital supply chain management, financial processes, and user experience. These challenges highlight the need for continuous improvement and adaptation to ensure the system’s long-term sustainability and effectiveness. The “Synchronized Scaling of Digital Fertilizer Advisory for Six Crops through Rwanda’s Smart Nkunganire System” project under the CGIAR Research Initiative Diversification for Resilient Agrifood Systems in East and Southern Africa (Ukama Ustawi) and Excellence in Agronomy (EiA) both supported by CGIAR led by International Potato Center (CIP) and other partners, aimed to address these challenges and explore optimal delivery/business models for the next phase of the SNS’s development. The assessment of various delivery/business models revealed that the SNS currently aligns most strongly with the Public-Private Partnership (PPP) and Mobile-First approaches. The PPP model has been instrumental in the system’s successful implementation, while the mobile-first design has enhanced its accessibility and reach. However, there is potential for the SNS to evolve further by incorporating elements of other models, such as tiered services and data monetization, to create a more personalized and impactful experience for farmers. The future of the SNS is promising. By addressing existing challenges, leveraging its data-driven insights, and exploring innovative business models, the SNS can continue to empower farmers, drive agricultural transformation, and contribute to Rwanda’s food security and economic growth. The key lies in fostering collaboration, investing in capacity building, and maintaining a steadfast commitment to user-centric design. The SNS stands as a testament to the transformative power of digital technology in agriculture and serves as a model for other countries seeking to enhance their agricultural sectors.